Penyuluhan Pemanfaatan Buah Ciplukan Sebagai Bahan Makanan Sehat Dengan Metode Jaga Jarak Fisik Akibat Wabah Covid 19 - Tajidan Tajidan; Arifuddin Sahidu; Suparmin Suparmin (Jurnal Gema Ngabdi, 2020)
In the situation of maintaining physical distance today requires all parties to innovate in carrying out activities including community service activities. The face to face method that has become a habit has to be changed by utilizing social media. One of the most widely used social media is WharsApp. In the context of disseminating information about the content and efficacy of ciplukan fruits, counseling was carried out using the physical distance keeping method through WhatsApp media. The results achieved from the implementation of counseling using social media WhatApp is increasing pesrta knowledge about the content and efficacy of ciplukan fruit respectively from 33.7% to 96.7% and from 53.3% to 86.7%, and increased interest in consuming fruit ciplukan from 67.9% to 93.3%.